(untitled) (Analysis in Theory and Applications, 2023)
We investigate the initial boundary value problem of some semilinear pseudo-parabolic equations with Newtonian nonlocal term. We establish a lower bound for the blow-up time if blow-up does occur. Also both the upper bound for T and blow up rate of the solution are given when J(u_0)